Navigating the Digital Health Landscape: A Professional's Guide to Choosing an AI-Powered Health App - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into digital health applications has ushered in a new era of personalized medicine, offering tools for everythi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine